Suppression effect of explosion in linked spherical vessels and pipelines impacted by wire‐mesh structure. Issue 1 (9th June 2015) - Zhang, Shangfeng; Wang, Zhirong; Zuo, Qingqing; Jiang, Juncheng; Cheng, Changde
Abstract : A series of experiments are conducted to study suppression effect of multilayer wire‐mesh structure on methane‐air mixture explosion in linked vessels. Explosion suppression effect is analyzed for explosion suppression structures with different layers and meshes. The most reasonable multilayer wire‐mesh structure is obtained. The multilayer wire‐mesh has a greater impact on explosion intensity in the big vessel than that in the small vessel. The combination of different layer number and mesh number has different explosion suppression effect on explosion. Mesh number has little effect on explosion pressure in both vessels when the layers are few. When the layers are more, the explosion pressure in both vessels is greatly impacted by mesh number. Under the condition of the same mesh number, the more the layers are, the better the explosion suppression effect. 5 and 7 are the critical explosion suppression layer number for 40‐mesh and 60‐mesh wire‐mesh structure, respectively. Compared with 5‐layer 40‐mesh wire‐mesh structure, the effect of 7‐layer 60‐mesh wire‐mesh structure on explosion suppression is better. So, in actual explosion protection design, the optional explosion suppression structure should be decided by taking into account of the comprehensive effect of layer number and mesh number. © 2015 American Institute of Chemical Engineers Process Saf Prog 35: 68–75, 2016